Comparative risk of musculoskeletal adverse reactions among new users of dipeptidyl peptidase-4 inhibitors: A retrospective cohort study - Taehwan Park; Maureen Bresnahan; Scott K. Griggs; Jiajing Chen; Alex H. Cho; Yolene Gousse; Mark Feinglos (Elsevier, 2021)
Background: The effects of dipeptidyl peptidase-4 inhibitors (DPP4Is) on joint pain have been controversial. Objective: To assess the comparative musculoskeletal (MSk) risk of DPP4Is vs. non-DPP4Is. Methods: This study used a national claims database from January 2007 to December 2014. Exposure included the initiation of DPP4Is against the initiation of non-DPP4Is: metformin, sulfonylureas, thiazolidinediones, meglitinides, and glucagonlike peptide-1 receptor agonists (GLP-1 RAs). Insulin was not included in this study. Outcomes were newly diagnosed MSk conditions (arthralgia, arthropathy, and rheumatoid arthritis or other inflammatory polyarthropathies). Individuals exposed to DPP4Is were matched to those exposed to non-DPP4Is using a propensity score (PS). Balance between the DPP4I's group and the non-DPP4I's group was assessed using standardized differences for both continuous and categorical variables. Cox regressions were used to estimate hazard ratios (HRs) for MSk conditions. Results: Among PS-matched cohorts, incidence rates (IRs) for MSk conditions did not differ between DPP4I initiators and non-DPP4I initiators (HR = 1.01, 95% CI: 0.97-1.05). After stratifying non-DPP4Is by drug class, the results still showed that DPP4I initiators had similar MSk risk when compared to initiators of metformin, sulfonylureas, meglitinides, and GLP-1 RAs. However, thiazolidinedione initiators had higher risk of MSk conditions than DPP4I initiators (HR = 1.05, 95% CI: 1.00-1.10). Conclusions: This head-to-head comparison study estimated comparative MSk risks among different antidiabetic drugs. The risk of MSk conditions among DPP4I initiators were not significantly higher than non-DPP4I initiators.